Tunable bandstop filter with high suppression and wide tuning range. Issue 16 (1st August 2019) - Li, Qun; Chen, Xiong; Yang, Tao
Abstract : A tunable bandstop filter (BSF) with high suppression and wide tuning range is presented. The tunable BSF includes nine pairs of coupling microstrip resonators. Each coupling microstrip resonator contains a back‐to‐back varactor pair and the voltage bias circuit is placed at the cathode of each varactor. Moreover, the back‐to‐back varactor pair is connected to an inductive terminal with two parallel metallised vias. Compared to a single metallised via, the inductance of two parallel metallised vias is reduced which can be beneficial to increase the stopband resonant frequency and improve the suppression level of the tunable BSF. Finally, a tunable BSF prototype with the tuning range of 3.8–9 GHz (81%) is fabricated. The measured suppression level is larger than 40 dB, over the entire tuning range.